Construction of recombinant Bacillus subtilis strains for efficient pimelic acid synthesis - Zhang, Wei-Wei; Yang, Ming-Ming; Li, Heng-xin; Wang, Dun (Electronic Journal of Biotechnology, 2011)
As a precursor, pimelic acid plays an important role in biotin biosynthesis pathway of Bacillus subtilis. Fermentations supplemented with pimelic acid could improve the production of biotin, however, with a disadvantage-high cost. So it is necessary to improve the biosynthesis of pimelic acid via genetic engineering in B. subtilis. In this study, we constructed a recombinant B. subtilis strain for improving the synthesis of pimelic acid, in which a maltose-inducible Pglv promoter was inserted into the upstream of the cistron bioI-orf2-orf3 and, meanwhile, flanked by the tandem cistrons via a single crossover event. The copy number of the integrant was amplified by high-concentration resistance screen and increased to 4-5 copies. The production of pimelic acid from multiple copies integrant was about 4 times higher than that from single copy (1017.13 μg/ml VS. 198.89 μg/ml). And when induced by maltose the production of pimelic acid was about 2 times of that under non-induction conditions (2360.73 μg/ml VS. 991.59 μg/ml). Thus, these results demonstrated that the production of pimelic acid was improved obviously through reconstructed B. subtilis. It also suggested that our expression system provided a convenient source of pimelic acid that would potentially lower the cost of production of biotin from engineered B. subtilis.